Prevalence of Prenatal Obsessive Compulsive Symptoms in Pregnant Women - Kiran, Tayyeba; Shafiq, Sameera; Anjum, Razia (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To explore the prevalence of prenatal obsessive compulsive symptoms in pregnant women, visiting various hospitals for obstetric checkups. METHODOLOGY: A Mixed Methods Design with qualitative and quantitative research approach was used. To develop Prenatal Obsession Compulsion Scale (POCS) in qualitative phase, 119 initial codes were generated through thematic analysis of literature review and transcriptions of in-depth semi structured interviews with psychiatrists, clinical psychologists and diagnosed pregnant women selected from hospitals of Lahore and Gujrat. In quantitative phase, these 119 items were reduced to 100 in content validation, carried out by experts. The preliminary 100-items of POCS finalized by expert content validity were administered to 300 pregnant women, selected by purposive sampling technique. Finalized, 40-items version of POCS, selected via exploratory and confirmatory factor analysis was administered on purposively sampled 352 pregnant women from private and government hospitals in January, 2019 till May, 2019. RESULTS: In sample of 352 pregnant women, 33.5% were between age 18 to 25 years. 89.5% were educated, 71.9% lived as house wives and 57.4% had joint family system. 40.9% had monthly income from 61,000 to 90,000 rupees. 58.2% had unplanned pregnancy and 32.1% had experienced first time pregnancy. Two hundreds and three pregnant women (57.7%), exhibited mild (n=59, 29.1%), moderate (n=73, 36.0%), severe (n=64, 31.5%), and extreme levels (n=7, 3.40%) of obsessive compulsive symptoms. The remaining 149 (42.3%) showed either subclinical or no symptoms of obsessions and compulsions. CONCLUSION: High prevalence of prenatal obsessive compulsive symptoms in pregnant women was found out empirically. KEYWORDS: Pregnant Women, Prenatal obsessive compulsive disorder, Prevalence.